Pengaruh Live Streaming Characteristics Dan Product Type Terhadap Impulsive Buying Melalui Trust Dan Flow Experience Dalam Live Streaming Commerce Pada Platform Tiktok Di Indonesia - Sunanto (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Live Streaming Commerce (LSC) has transformed consumer shopping behavior by integrating real-time interactivity in digital. This study uses the Stimulus-Organism-Response (S-O-R) framework to analyze how product types (utilitarian and hedonic) and LSC characteristics (social presence, personalization, and entertainment) influence impulsive buying through trust (cognitive trust and emotional trust) and flow experience, which includes enjoyment and concentration. Quantitative data were collected from 375 Gen Z and Millennial respondents who are active TikTok users in Indonesia as an LSC platform. Structural Equation Modeling (SEM) analysis reveals that utilitarian products positively influence cognitive trust but negatively influence emotional trust. In contrast, hedonic products positively influence both. Social presence and entertainment characteristics have a positive impact on enjoyment and concentration, while personalization is not significant for enjoyment and negatively affects concentration. Emotional trust and enjoyment positively influence impulsive buying, while cognitive trust and concentration have no significant impact. These findings contribute theoretically to consumer behavior literature and offer practical implications for marketers in designing more effective strategies on the LSC platform.